2020
DOI: 10.2196/17103
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between State-Level Racial Attitudes Assessed From Twitter Data and Adverse Birth Outcomes: Observational Study

Abstract: Background In the United States, racial disparities in birth outcomes persist and have been widening. Interpersonal and structural racism are leading explanations for the continuing racial disparities in birth outcomes, but research to confirm the role of racism and evaluate trends in the impact of racism on health outcomes has been hampered by the challenge of measuring racism. Most research on discrimination relies on self-reported experienc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 40 publications
(49 reference statements)
0
45
0
1
Order By: Relevance
“…A rise in negative racial attitudes and racial bias can have significant social, economic, and mental and physical health impacts [ 6 , 7 , 8 ]. Prior research has shown that community-level racial climate is related to birth outcomes [ 9 , 10 , 11 ], cardiovascular outcomes [ 12 ], and mortality [ 13 ] of the area. Such attitudes reflect cultural racism, defined as the infusion of the ideology of racial inferiority in the values, language, imagery, symbols, and unstated assumptions of the larger society [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rise in negative racial attitudes and racial bias can have significant social, economic, and mental and physical health impacts [ 6 , 7 , 8 ]. Prior research has shown that community-level racial climate is related to birth outcomes [ 9 , 10 , 11 ], cardiovascular outcomes [ 12 ], and mortality [ 13 ] of the area. Such attitudes reflect cultural racism, defined as the infusion of the ideology of racial inferiority in the values, language, imagery, symbols, and unstated assumptions of the larger society [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the need for more extended studies is urgent, as numbers of disparities have been increasing over the years. Nguyen et al ( 27 , 28 ), tried to identify the connection between state-level Twitter-derived sentiments and racial or ethnic disparities in birth outcomes. More specifically, researchers collected 26.027.740 relevant tweets from June 2015 to December 2017 and conducted sentiment analysis using a supervised machine learning model (Support Vector Machine).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a multilevel survival analysis, Lee and colleagues found community-level racial bias was associated with mortality independent of individual-level racial bias ( Lee, Muennig, Kawachi, & Hatzenbuehler, 2015 ). Emerging work has also shown that area-level racial bias is associated with worse health outcomes for both racial/ethnic minorities as well as Whites ( Leitner et al, 2016 ; T.; Nguyen et al, 2020 ; Nguyen et al, 2018 ). Taken together, the growing body of evidence indicates the potential influence of area-level racial bias on the health of communities.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a sentiment analysis on the Twitter data set. This procedure has been previously described ( Nguyen et al, 2020 ). Briefly, we utilized Support Vector Machines (SVM), a supervised machine learning model to label the tweets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation